Puppet Accountant - Muhammad Aras Prabowo; Dewi Nisaul Mukaromah; Mariska Nur Hanifa; Windu Mulyasari; Mohd Rushdan Yasoa (Trescode Green Organization, 2025)
This research examines the application of accounting principles to Javanese cultural values ​​reflected in wayang art, as well as the importance of maintaining and implementing cultural codes of ethics in preserving this valuable cultural heritage. This approach is carried out through a literature review in a systematic process to identify and synthesize relevant research on the topic. The results of the literature review show the character values ​​found in wayang. Analyzing various related documents to understand Javanese cultural values ​​and wayang characters. This research identifies five wayang values ​​in Javanese society to strengthen the guidelines for the code of ethics for accountants. These values ​​include: (1) Responsibility (tanggung jawab) (2) Mutual cooperation (Gotong royong) (3) Be careful (Ati-ati) (4) Be firm (Teges) (5) Be wise (sikap wicaksana). These five values ​​can strengthen the implications of this research, including efforts to increase public understanding of the values ​​of Javanese wayang culture.